PENGEMBANGAN MAGIC CROSSWORD PUZZLE SEBAGAI MEDIA PEMBELAJARAN IPA UNTUK SISWA KELAS V SEKOLAH DASAR - Ifa Seftia Rakhma; Unik Widyaningsih; Lilik Mawartiningsih (Universitas Muria Kudus, 2017)
The purpose of this research is to develop magic crossword puzzle media in the material of natural phenomena. This research is a Research and Development. Implementation magic crossword puzzle media using one group pretest-posttest control design with the subjects are fifth grade students SDN 2 Gedong Mulyo Mulyo academic year 2016/ 2017. The results magic crossword puzzle media consists of two parts, front page and back page. The front page is crossword puzzle and the back page is pieces of pape. The results validate from two validators are media developed by the researchers included in the category of valid use in the fiftth grade of elementary school. Magic crossword puzzle effective in material natural phenomena from the pretest result is 55,56 % posttest result is 94,4 %. Students activity is 32 % and teacher activity is 38 %. Students also give good respon to magic crossword puzzle meda.